Existentialist Characters in Munir Ahmad Badini’s Writings - Ali, Asghar (Hanken, 2013)
Munir Ahmad Badini is one of the leading novelists and short story writer in the Balochi Literature for all time. No doubt, he is a well-skilled mastery over the act of characterization. This paper focuses and dissects some of his Novel’s characters that how far they are existentialist in nature. Furthermore, it highlights how characters of Munir Badini’s novels in a constant war of self-realization, vice and virtue, bad faith and anguish. Consequently, it is clear that his characters are completely germane to, or speak and act in the line of existentialist philosophy expounded by J.P. Sartre.